Application of E-Tendering in Malaysia Construction Industry - Tan, Jeffrey Jia Ren (2015)
Electronic tendering has been assumed to be a more effective method compare with traditional tendering method. However, most of the local projects are still adopting traditional tendering method. The aim of this study is to investigate whether the contractors in Malaysia construction industry would adopt and participate in e-tendering system. The study will takes into account the application of c-tendering in current Malaysia construction industry, the challenges of implementing c-tendering system and willingness of the contractors to participate in c-tendering. The research used online questionnaire survey to identify the level of understanding about e-tendering system of contractors in Malaysia and also whether the contractors involved in the application of c-tendering in Malaysia. The result shows that the application of c-tendering is in moderate level in current Malaysia construction community. Majority of the contractors have moderate understanding regarding c-tendering system and more than half of them having experience with c-tendering. The challenges of e-tendering system were also evaluate. There are several challenges for example resistance to change, lack of knowledge, high maintenance cost, high initial cost, poor reliability, lack of business relationship, security concern, and legal issues. Through questionnaire, the contractors have been asked to rank the challenges based on their opinions or experiences in the industry. Poor reliability, security concern and resistance to change have the highest ranking among all the challenges. Contractor’s willingness to adopt e-tendering was also evaluated. Most of the contractors are willing to involve if they are invited to participate in the c-tendering project. Saving in storage space is one of the biggest factors which contribute to the contractors’ willingness to participate in c-tendering. In other hand, security concern is the most important factor contributes to contractors’ unwillingness in the participation of e-tendering.